Banking Transaction Trends Among Gen Z: A Comparative Study Between Conventional Banks and Islamic Banks - Amanda; Mailindra, Wiyan (Jurnal Iqtisaduna, 2025)
This study examines the factors influencing Generation Z’s preferences in selecting banking services and their level of understanding of Islamic banking systems. Employing a qualitative approach, in-depth interviews were conducted with 20 respondents who actively use banking services. Findings reveal that the majority of participants prefer conventional banks over Islamic banks, primarily due to easier access to digital services, a wider ATM network, and more competitive administrative costs. Nevertheless, some respondents still consider sharia principles in their banking choices. The results underscore the necessity of enhancing Islamic financial literacy and advancing technological innovation to better engage Generation Z.